CREATIVITY AND INNOVATION TO COMPETE IN THE CENTURY 21 (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Competition for a decent life depends on the creativity and ability to innovate. This condition is caused by countries that have superior human resources will be more advanced than in countries with a lot of natural resources but is not reliable. In the future we will face some challenges that require changes in traditional educational paradigm that has been applied by teachers in Indonesia. To that end, students should be accustomed to searching for information themselves, able to identify and formulate problems, able to work effectively in groups and build networks, as well as high creativity mimiliki. In order for creativity and innovation with the optimal form then students must be equipped with the knowledge, attitude and skills are adequate to face the challenges of today and in the future.